2016
DOI: 10.1016/j.rmed.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Subjects with well-controlled asthma have similar health-related quality of life as subjects without asthma

Abstract: The physical score was significantly lower in asthmatics compared to subjects without asthma. Importantly, non-smoking and well-controlled asthmatics have similar HRQL compared to subjects without asthma. Thus, subjects with asthma should be supported to achieve and maintain good asthma control and if they smoke, be offered smoking cessation as means to improve their HRQL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…According to Stephen et al () nursing‐led intervention in primary care, such as support to quit smoking, increased physical activity, or weight management can reduce lifestyle risk factors and improve health outcomes. Overall in our study, 10% of the individuals with asthma were daily smokers, with higher prevalence among women than among men, similar to other studies from the Nordic countries (Jansson et al, ; Tollefsen et al, ). Smoking was associated with uncontrolled asthma, also after adjustment for covariates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to Stephen et al () nursing‐led intervention in primary care, such as support to quit smoking, increased physical activity, or weight management can reduce lifestyle risk factors and improve health outcomes. Overall in our study, 10% of the individuals with asthma were daily smokers, with higher prevalence among women than among men, similar to other studies from the Nordic countries (Jansson et al, ; Tollefsen et al, ). Smoking was associated with uncontrolled asthma, also after adjustment for covariates.…”
Section: Discussionsupporting
confidence: 92%
“…ACT is shown to be a reliable and valid tool for evaluating and discriminating asthma control (Nathan et al, ), with high internal consistency reliability (Axelsson et al, ; Nathan et al, ). ACT is also commonly used in Swedish studies (Axelsson et al, ; Jansson et al, ; Stridsman et al, ). Furthermore, the prevalence of current asthma in our study is in line with previous reports (Lötvall et al, ), which strengthens the generalizability of our results.…”
Section: The Studymentioning
confidence: 99%
“…Fig 3 shows the distance between our sample and reference norms according to asthma control. These findings are in agreement with the 2008 European National Health and Wellness Survey [ 15 ] and a randomly selected cohort with clinical examination [ 38 ], in which well-controlled asthma patients presented similar SF-12 scores to the general population.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously shown that adults with wellcontrolled asthma report similar health status as those without asthma (32). Others have shown that poor asthma control is related to worse health status, together with factors as advancing age and lower educational level (33).…”
Section: Discussionmentioning
confidence: 91%